2001
DOI: 10.1021/jp010281c
|View full text |Cite
|
Sign up to set email alerts
|

ESR and Optical Properties of Copper Atoms in γ-Irradiated Organic Solutions at 77 K

Abstract: EtOH and MTHF solutions containing Cu + ions are γ-irradiated at 77 K. ESR spectra are attributed, for the first time, to Cu 0 that is produced radiation-chemically by reducing Cu + ions in the solutions at 77 K. A large delocalization of the unpaired spin density of Cu 0 onto ligands is deduced. No evidence for formation of the dimer cation of Cu 0 has been obtained. This is contrary to the case of Ag 0 produced in the solutions containing Ag + ions. The NUV absorption spectrum of Cu 0 is decomposed into five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 27 publications
8
15
1
Order By: Relevance
“…We will mention this later in detail. The ESR spectra obtained after irradiation in the present study subsequent to uv irradiation were the same as those reported previously [10]. As shown in spectra (c) in Figs.…”
Section: Esr Propertiessupporting
confidence: 83%
See 4 more Smart Citations
“…We will mention this later in detail. The ESR spectra obtained after irradiation in the present study subsequent to uv irradiation were the same as those reported previously [10]. As shown in spectra (c) in Figs.…”
Section: Esr Propertiessupporting
confidence: 83%
“…We also proved experimentally that an admixture of the wave function of the Cu 0 atom in its ground state 2S 1/2 : 3d 10 4s 1 into 3d x 2 y 2 is expected to occur to some extent. The five nuv absorption bands represented as bands from C 1 to C 5 were observed after irradiation in the organic solid solutions at 77K [10]. We attributed them to the two types of exciplexes formed between excited Cu 0 atoms and the ligands: one associates with Cu + ions as well as solvent molecules, the other consists mainly of solvent molecules.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations